Toxic leadership and quiet quitting in muslim workplaces: The moderating role of monetary rewards - Baharudin, Baharudin; Budiman, Budiman; Aziz, Muhammad Iqbal; Hartati, Sri (Psikis : Jurnal Psikologi Islami, 2025)
Quiet quitting presents a growing challenge in the healthcare sector, adversely affecting both employee performance and overall organizational outcomes. From an Islamic perspective, quiet quitting can be understood as a manifestation of the erosion of niyyah (intentionality) and ikhlāṣ (sincerity) in one’s professional duties. This study examined the influence of toxic leadership on quiet quitting among muslim healthcare professionals, with a particular focus on the mediating role of monetary incentives. Data were collected from 104 full-time muslim staff members employed in hospitals and healthcare training institutions in Palembang City through a targeted online survey. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that toxic leadership has a significant negative effect on perceptions of monetary rewards (β = -0.316) and a positive effect on quiet quitting behavior (β = 0.292). Moreover, monetary rewards showed a strong relationship with quiet quitting outcomes (β = 0.669). The indirect effect of toxic leadership on quiet quitting through monetary rewards (β = -0.212) suggested that toxic leadership diminishes the motivational value of compensation, thereby increasing disengagement. Collectively, toxic leadership and monetary rewards explained 41% of the variance in quiet quitting. These findings highlighted the need for healthcare organizations to implement leadership development programs and establish transparent, fair reward systems. Integrating ethical principles particularly those rooted in Islamic values of justice (ʿadl), trust (amānah), and sincerity (ikhlāṣ) can help address leadership deficiencies and foster a workplace environment that promotes commitment, cooperation, and excellence.